If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8Y + 7 = 14Y + 7 Reorder the terms: 7 + 8Y = 14Y + 7 Reorder the terms: 7 + 8Y = 7 + 14Y Add '-7' to each side of the equation. 7 + -7 + 8Y = 7 + -7 + 14Y Combine like terms: 7 + -7 = 0 0 + 8Y = 7 + -7 + 14Y 8Y = 7 + -7 + 14Y Combine like terms: 7 + -7 = 0 8Y = 0 + 14Y 8Y = 14Y Solving 8Y = 14Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-14Y' to each side of the equation. 8Y + -14Y = 14Y + -14Y Combine like terms: 8Y + -14Y = -6Y -6Y = 14Y + -14Y Combine like terms: 14Y + -14Y = 0 -6Y = 0 Divide each side by '-6'. Y = 0 Simplifying Y = 0
| (7x-9)(3x+8)=0 | | 20a^3-41a^2+20a=0 | | 4X*X+X-3=0 | | X*X+X-2=0 | | -21x^2+23x-6=0 | | -9x^2+15x+14=0 | | 14x+2y=-10 | | 28x^3+19x^2+3x=0 | | 178-53-x+4= | | -10x=80 | | -7=x-2 | | y=8x^2+16x-3 | | x-6=5+(-4) | | x(0.1x-1)=0.00000014 | | y+3=8 | | 7t^2-31t-20=0 | | a^2-10a+24= | | 35-17=2(x-2) | | 0.1x^2-x=0.00000014 | | 3t^2-19t-40=0 | | -0.6x-0.05x^2+32=0 | | 7-3+3*0= | | 4(b-8)=(4+7)b | | 6n=-30 | | n+8=-6 | | 9b^2-24b-105=0 | | -5x^2+6x-27=0 | | -5x^2+6x+23=0 | | 5x+32x-4=5x+32-4x | | 3x+7=2x-12 | | 2z^2-20z-50=-512 | | x+8y=-32 |